The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1111/j.1442-9071.1993.tb00961.x
|View full text |Cite
|
Sign up to set email alerts
|

Endophthalmitis in Auckland 1983–1991

Abstract: A review was made of 58 cases of suspected endophthalmitis presenting to Auckland Public Hospital between January 1983 and July 1991 (103 months). Thirty culture positive cases were found comprising 13 early onset postoperative, six delayed onset postoperative, five bleb-associated, four post-traumatic and two endogenous cases. The most frequent organism grown in postoperative en do p h t h al m i t is was Staphylococcus epidermidis. No conclusion could be reached as to the effectiveness of early versus delaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 44 publications
(5 reference statements)
2
7
0
Order By: Relevance
“…The results of this study are consistent with other reports finding BRE as the second most common form of infectious endophthalmitis, after acute and chronic post-cataract surgery Endophthalmitis 1. BRE usually develop late (>1month) but in our series 15% of the cases had BRE earlier (< 2weeks).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of this study are consistent with other reports finding BRE as the second most common form of infectious endophthalmitis, after acute and chronic post-cataract surgery Endophthalmitis 1. BRE usually develop late (>1month) but in our series 15% of the cases had BRE earlier (< 2weeks).…”
Section: Discussionsupporting
confidence: 92%
“…Bleb-related endophthalmitis (BRE) is the second most frequent (16.7%) cause of postoperative endophthalmitis after acute and chronic post-cataract surgery endophthalmitis 1. It's incidence is reported to be between 0.2% to 1.3%,23 and is more common with the use of antiproliferative agent (up to 3%) and even higher when the bleb is placed inferiorly (up to 9.4%) 47.…”
mentioning
confidence: 99%
“…is the most common cause of acute-onset postoperative endophthalmitis following cataract surgery [6-8]. Series from Australia [9,10], North America [6], and Europe [11,12] have reported 6% to 12% Gram-negative bacteria and in the EVS reporting Gram-negative bacteria was isolated in 5.9% (19/323) eyes [5]. The Indian studies, at 26% to 42%, have reported higher incidences of Gram-negative bacterial infection [1,2].…”
Section: Resultsmentioning
confidence: 99%
“…Although vitreous samples are of greater benefit the value of aqueous and capsule/IOL culture should not be underestimated. Kent et al found aqueous samples to be positive by culture in eight cases when culture of vitreous proved unhelpful24 and Busin et al used scanning electron microscopy and detected bacteria on all removed lenses in 11 patients in whom cultures were negative before IOL removal, five of which were culture positive from samples taken at the time of IOL removal 25…”
Section: Discussionmentioning
confidence: 99%